PENGARUH PENGETAHUAN AKUNTANSI DAN JIWA KEWIRAUSAHAAN PADA PENGGUNAAN INFORMASI AKUNTANSI DALAM PEMBUATAN KEPUTUSAN INVESTASI - Juniariani, Ni Made Rai; Wirakusuma, Made Gede (Buletin Studi Ekonomi; VOL.21.NO.2.AGUSTUS 2016 (PP 115-232), 2017)
Abstract: The Influence Of Accounting Knowledge and Entrepreneurship In The Use Of AccountingInformation In Making Investment Decision. The first purpose of this research is testing the influenceof accounting knowledge in the use of accounting information in making investment decision. TheSecondth purpose is testing the influence of entrepreneurship in the use of accounting information inmaking investment decision. The primary data be used in this researchis in the form of answers toquestionnaire from customers of PT. Permodalan Nasional Madani (Persero) per December 31 2015 usingthe survey method.98 samples were obtained using the saturated sample methods or census methods.This research using multiple linear regression analysis. The hypothesis test results are the accountingknowledge is affection the use of accounting information in making invesment decision. The entrepreneurship is affect on the use of accounting information in making invesment decision. Studies have shownthe importance of accounting knowledge and the entrepreneur ship for UMKM entrepreneur in the useof accounting information in making investment decision for the future of his business.Keywords: accounting knowledge, entrepreneurship, accounting information in making invesmentdecision. Abstrak: Pengaruh Pengetahuan Akuntansi Dan Jiwa Kewirausahaan Pada Penggunaan InformasiAkuntansi Dalam Pembuatan Keputusan Investasi. Penelitian ini memiliki dua tujuan. Pertama, untukmembuktikan pengaruh pengetahuan akuntansi pada penggunaan informasi akuntansi dalam pembuatankeputusan investasi. Kedua, pengaruh jiwa kewirausahaan pada penggunaan informasi akuntansi dalampembuatan keputusan investasi. Data primer berupa jawaban kuesioner dari nasabah PT. PNM UnitSukawati dengan menggunakan metode survei digunakan dalam penelitian ini. .98 sampel diperolehdengan menggunakan metode sampling jenuh atau metode sensus. Metode analisis penelitian inimenggunakan analisis regresi linear berganda. Hasil pengujian hipotesis menunjukkan bahwapengetahuan akuntansi berpengaruh positif pada penggunaan informasi akuntansi dalam pembuatankeputusan investasi. Jiwa kewirausahaan berpengaruh positif pada penggunaan informasi akuntansidalam pembuatan keputusan investasi. Penelitian membuktikan pentingnya pengetahuan tentangakuntansi dan jiwa kewirausahaan bagi pengusaha dalam membuat keputusan investasi untuk masadepan usahanya.
Keywords: accounting knowledge, entrepreneurship, accounting information in making invesment decision.